2020
DOI: 10.1002/jbm.a.36974
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial graphene‐based hydroxyapatite/chitosan coating with gentamicin for potential applications in bone tissue engineering

Abstract: Electrophoretic deposition process (EPD) was successfully used for obtaining graphene (Gr)‐reinforced composite coating based on hydroxyapatite (HAP), chitosan (CS), and antibiotic gentamicin (Gent), from aqueous suspension. The deposition process was performed as a single step process at a constant voltage (5 V, deposition time 12 min) on pure titanium foils. The influence of graphene was examined through detailed physicochemical and biological characterization. Fourier transform infrared spectroscopy, field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…We observed that the zones were the same after 5 days of incubation and 11 days of incubation. These results are in line with previous studies on antibiotic coatings against S. aureus and other bacteria [17,18,81].…”
Section: Antibacterial Evaluationssupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that the zones were the same after 5 days of incubation and 11 days of incubation. These results are in line with previous studies on antibiotic coatings against S. aureus and other bacteria [17,18,81].…”
Section: Antibacterial Evaluationssupporting
confidence: 93%
“…We observed that the zones were the same after 5 days of incubation and 11 days of incubation. These results are in line with previous studies on antibiotic coatings against S. aureus and other bacteria [17,18,81]. When examining the antibacterial effect by means of the broth dilution method, the PEEK-HAP1-Cef sample possessed a higher antibacterial effect against S. aureus compared to PEEK-HAP1 and the control sample (PEEK only; Figure 9A).…”
Section: Antibacterial Evaluationssupporting
confidence: 91%
“…Above everything mentioned before, chitosan has very high position in the field of biomaterials production due to its exceptional properties of easy film forming ability [ 57 , 70 ]. Chitosan, as a cationic polysaccharide, can be used in the electrophoretic deposition process (EPD), one of the most attractive techniques for bioactive coatings production [ 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Lignin (Lig) is a polyphenolic polymer, originated from the various natural sources [ 78 , 79 , 80 ].…”
Section: Engineering Implant Surfaces To Prevent Microbial Adhesion and Infectionmentioning
confidence: 99%
“…Composite coatings on Ti were electrophoretically deposited from two different aqueous suspensions, HAP/CS/Gent (1 wt.% of HAP, 0.05 wt.% of CS and 0.1 wt.% of Gent) and HAP/CS/Gr/Gent (1 wt.% of HAP, 0.05 wt.% of CS, 0.01 wt.% of Gr, and 0.1 wt.% of Gent). A three-electrode cell arrangement, e.g., titanium plate as a working electrode and two Pt panels as counter electrodes were employed to deposit composite coatings at room temperature, constant voltage of 5 V and deposition time of 12 min [ 68 , 71 , 72 ].…”
Section: Designing Coatings With Long-term Release Of Antibioticsmentioning
confidence: 99%
“…These include the presence of amorphous phases resulting from the extremely high process temperatures [26] and the difficulty of coating implants with complex geometrical features due to the line-of-sight nature of the process [27]. Alternative methods include: Sol-gel processing [28,29], biomimetic deposition [30][31][32], hydrothermal processing [33], electrophoresis [34], gas detonation deposition [35][36][37], and electrodeposition [38][39][40]. Among these, electrodeposition is the most promising technique because it can deposit homogeneous HAp coatings on interior and exterior surfaces of metallic scaffolds, regardless of a sample's size or pore geometry.…”
Section: Introductionmentioning
confidence: 99%